A complex case of acute abdomen - Mohammed Khalid Alageel (International Journal of Emergency Medicine)
Abstract Introduction Acute abdomen during early pregnancy poses a diagnostic challenge, especially in patients with underlying chronic gastrointestinal diseases. Case report A 36-year-old woman with Crohn’s disease and a confirmed 6-week intrauterine pregnancy presented with diffuse abdominal pain. Initial investigations, including MRI and ultrasound, were inconclusive. Diagnostic laparoscopy revealed malrotation of the large bowel and a perforated appendix, which was successfully managed with appendectomy and lavage. Conclusion This case highlights the diagnostic complexity of abdominal pain in early pregnancy, particularly in patients with Crohn’s disease and anatomic variations such as intestinal malrotation.